Design and Optimization of Thermo-reversible Nasal in situ Gel of Atomoxetine Hydrochloride Using Taguchi Orthogonal Array Design - Lakshmi, PK; Harini, K (Dhaka University Journal of Pharmaceutical Sciences, 2019)
The present investigation was aimed to develop a thermo-reversible nasal in situ gel of atomoxetine hydrochloride (AH) with reduced nasal muco-ciliary clearance in order to improve residence time and targeting the brain through nasal mucosa for the treatment of attention-deficit hyperactivity disorder (ADHD). In situ gel formulations were prepared using different concentrations of the thermo-gelling poloxamer 407 and mucoadhesive polymers. Temperature-triggered ionic gelation is the mechanism involved. Taguchi L9 OA experimental design was employed for the optimization of the effect of independent variables (Poloxamer 407 and Carbopol 934P) on the response (gelation temperature). In situ gel formulation F4 having 20% poloxamer 407 and 0.3% carbopol 934P and formulation F6 having 20% poloxamer 407 and 0.2% HPMC K100 were optimized based on evaluation parameters. The gelation temperature of F4 and F6 was found to be 37°C ± 0.4 and 37°C ± 0.2, drug content 98.34 and 98.33% and drug release was 83.18, 82.4% in 4 hrs with a flux of 436.9 and 428.1 μg.cm2/hr, respectively. The release pattern of drug followed first-order kinetics with Higuchi release mechanism. The value of ‘n’ from Korsemeyer equation indicated the anomalous diffusional drug release. This study concluded that in situ gel enhanced the nasal residence time and thus may improve the bioavailability of the drug through nasal route by avoiding first pass metabolism Dhaka Univ. J. Pharm. Sci. 18(2): 183-193, 2019 (December)